Factors that Contribute to the Adjustment of International Students - Mesidor, Jean Kesnold; Sly, Kaye F. (Journal of International Students, 2016)
Leaving home to attend college is an important milestone for college students. However, the transition from home to college can be challenging, especially for students studying abroad. In this article, the authors explore factors that contribute to the academic, cultural, social, and psychological adjustments of international students. Adjustment issues include psychological distress such as homesick, depression, and anxiety. This article seeks to increase the reader’s understanding of some of the issues faced by international students during the process of adjusting to a new collegiate environment. More specifically, the article discusses factors that contribute to adjustment and different phases of cultural adjustment. This article may help the students, educational institutions, and policy makers to provide the resources necessary for a seamless transition for international students to overcome the issues.